2018
DOI: 10.2174/0929867325666180214115438
|View full text |Cite
|
Sign up to set email alerts
|

Activators of Sirtuin-1 and their Involvement in Cardioprotection

Abstract: SIRT1 is a nicotinamide adenosine dinucleotide (NAD+)-dependent deacetylase, which removes acetyl groups from many target proteins, such as histone proteins, transcription factors and cofactors. SIRT1-catalyzed deacetylation of these factors modulates the activity of downstream proteins, thus influencing many biological processes. SIRT1 is involved in the regulation of metabolism, inflammation, and tumor growth. The activity of this enzyme is related to the beneficial health effects of calorie restriction, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 111 publications
2
13
0
Order By: Relevance
“…The sirt-1 activator SRT2104, similar to other sirt-1 activators, increased mitochondrial content and suppressed the inflammation pathways [32]. It also exhibits endothelial protective effects which is observed in this study [32].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The sirt-1 activator SRT2104, similar to other sirt-1 activators, increased mitochondrial content and suppressed the inflammation pathways [32]. It also exhibits endothelial protective effects which is observed in this study [32].…”
Section: Discussionsupporting
confidence: 69%
“…When the PTP opens, the contact between the cytosolic and the mitochondrial pools of pyridine nucleotides may reduce NAD + via enzymatic reactions [25]. The sirt-1 activator SRT2104, similar to other sirt-1 activators, increased mitochondrial content and suppressed the inflammation pathways [32]. It also exhibits endothelial protective effects which is observed in this study [32].…”
Section: Discussionsupporting
confidence: 63%
“…In red wine, the concentration of resveratrol varies from 0.09 to 18 mg/L (average of 5 mg/L) 9 . The resveratrol (3,5,4'-trihydroxy-trans-stilbene) is a small molecule with a molecular weight of 228.246 g/mol with anti-inflammatory, antioxidant, hypoglycemic and antihypertensive and cardioprotective effects, which acts through multiple mechanisms of action, including the activation of the silent information regulator factor 2-related enzyme 1 (Sirt1), a nicotinamide adenine dinucleotide-dependent deacetylase involved in many physiological functions like oxidative stress [9][10][11][12][13][14] . Based on our recent studies, we have suggested that the combined molecular actions of resveratrol on Sirt1 and other cellular proteins involved in the regulation of functions of cardiac cells stimulates the cardioprotective response, attenuating or preventing the cytosolic and mitochondrial Ca 2+ overload and bioenergetic collapse involved in cardiac arrhythmias caused by ischemia and reperfusion in cardiac cells 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its role in the physiological processes, SIRT1 plays a key role in various diseases, such as diabetes, obesity, cancer, neurodegenerative and cardiovascular diseases, and age-related pathologies [19].…”
Section: Introductionmentioning
confidence: 99%